ART IN ISLAM: BEAUTY AS INVITATION – A PHILOSOPHICAL AND SOCIOLOGICAL STUDY OF ISLAMIC ART AS A FORM OF DA ‘WAH IN CONTEMPORARY SOCIETY - Dheen Muhammedh (JCI Publisher, 2026)
Attraction to the beauty, pattern and symbolism of Islamic Art can draw observers to considerations of the divine. Beauty can serve to reflect the communication of Islam. This study explores the philosophical concepts of tawḥīd, or iḥsān and fiṭrah and the sociological concepts of reception and Cultural Translation to posit Islamic Art as the Islamic pedagogy of moral philosophy of art, a pedagogy of Islamic artistic inter-religious dialogue. Using Islamic calligraphy, mosque architecture and digital art as evidencebased qualitative research, the study documents the fit of the proposition and the aesthetic joys of art in beauty as a lingua franca of faith inter-culture. The study documents the experience of the ethics of Islamic Art as compassion in voiceless daʿwah. The aesthetic of Islamic Art becomes the moral pedagogy of spiritual compassion and the daʿwah aesthetic of work converted to the experience of beauty. The study proposes the lived experience of sincerity as beauty, unrivaled, is one of the most persuasive communications of Islam in the modern world in the compassionate and loving distance of the ethical.